Crimmigrant nations : resurgent nationalism and the closing of borders - Koulish, Robert E. (Robert Edwin); Woude, Maartje Amalia Hermina van der, 1980- (Fordham University Press, 2020)
A timely examination of the increasing efforts to criminalize the status of immigrants, exiles, and refugees.